1995
DOI: 10.1271/bbb.59.1766
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Dimethylamino Group and Macrodiolide Ring of Pamamycin-607 in Its Aerial Mycelium-inducing Activity

Abstract: Four pamamyciu..(j07-degraded products-desdimethylaminopamamycin-607, a macrodiolide ring-opened compound, and two constitutent hydroxy acids-were prepared, and their aerial mycelium-inducing activity was measured. The hydroxy acid L part with a dimethyl amino group was the principal component responsible for activity. The macrodiolide ring itself was dispensable, but only hydroxy acid L showed very weak activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…This regulatory mechanism of pamamycin production is reasonable because introduction of a nitrogen atom has been reported to be essential for aerial mycelium-inducing activity [6,10].…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…This regulatory mechanism of pamamycin production is reasonable because introduction of a nitrogen atom has been reported to be essential for aerial mycelium-inducing activity [6,10].…”
Section: Discussionmentioning
confidence: 89%
“…These results showed that 7 was incorporated into 1. 13 C-labeled 7 with 5 also increased intensities of isotope peaks of de-N-methylpamamycin (6) in cultured materials (data not shown).…”
Section: Bioconversion Of De-n-methylpamamycin (6) and De-nmethylhydrmentioning
confidence: 84%
See 3 more Smart Citations